Echocardiographic Evaluation of Left Ventricular Mass Among Adult Bangladeshi Population - Sultana, Abeda; (Ujjal), Saleh Uddin Siddique; Rahim, M A; Chowdhury, Urmila; Das, Rakesh Kumar; Ashrafuzzaman, Md (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Left Ventricular Mass (LVM) refers to the weight of the left ventricle, which is determined using echocardiography. Various studies regarding LVM were conducted in different countries. There is a lack of data on LVM in our country. The current study aimed to provide baseline normative data on LVM among the adult Bangladeshi population. Materials and methods: This descriptive cross-sectional study included 100 adults who had normal echocardiography from the Outpatient Department of Cardiology and Medicine of Chittagong Medical College Hospital. Results: Overall, LVM ranged from 63.90 gm to 186.58 gm with a mean ±SD of 123.55±24.38gm. The mean ± SD of LVM in males was significantly higher than female (136.30±20.65 vs. 110.80±21.03 gm, p<0.001). There was a significant positive correlation between age and LVM (r=0.612, r 2 =0.374, p<0.001) and between BMI and LVM of the participants [r = 0.393, r 2 =0.154, p<0.001]. About 37% and 15% variability of the LVM of an individual could be explained by their age and BMI respectively. Conclusion: The normal LVM in Bangladeshi adult population was found to be higher in male and LVM increased with increasing age and BMI. JCMCTA 2024 ; 35 (2) : 146-149